Scientific Approach in Islamic Mathematics E-Modules for Sequences and Series: A Decade's Systematic Review - Hanisa Hanisa; Baharullah Baharullah; Andi Husniati (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2026)
Mathematics education tools in the digital age predominantly emphasize cognitive skills, frequently neglecting character development and spiritual values. Consequently, learning often feels rigid and disconnected from real-life contexts due to a scarcity of instructional materials that seamlessly integrate scientific methods with Islamic principles. This Systematic Literature Review (SLR) investigates the development, characteristics, and effectiveness of Islamic value-based mathematics e-modules specifically focused on sequences and series topics published over the past decade. Following rigorous inclusion criteria, 22 high-quality empirical studies were selected from Google Scholar, ERIC, SINTA, and Scopus, with 50% indexed in Scopus and SINTA 1 and 2. Findings reveal that Islamic values are organically embedded across the 5M scientific framework; for instance, contextualizing sequence and series concepts as expressions of divine justice. Technologically, Flipbook-based platforms (45%) and interactive multimedia (27%) emerged as the primary delivery formats. Meta-analytical data demonstrates that implementing these e-modules yields substantial improvements: religious character achieved the highest normalized gain (N"-Gain"=0.82), followed by conceptual understanding (0.74) and learning autonomy (0.68), all falling within the high-effectiveness category. Although highly effective at imbuing abstract concepts with deeper spiritual meaning, significant research gaps remain regarding the integration of advanced technologies like augmented reality (AR). This study offers key theoretical insights for science-religion integrated curricula and actionable guidance for designing modern, spiritually aligned instructional media.